RADT-05. VOLUMETRIC MODULATED ARC THERAPY CRANIOSPINAL IRRADIATION UTILIZING A VERTEBRAL BODY SPARING APPROACH: A DOSIMETRIC ANALYSIS. (14th November 2022) - Matsui, Jennifer; Perlow, Haley; Ewing, Ashlee; Cadieux, Catherine; Blakaj, Dukagjin; Beyer, Sasha; Thomas, Evan; Raval, Raju; Palmer, Joshua
Abstract: BACKGROUND: Craniospinal irradiation (CSI) is indicated for adult patients diagnosed with leptomeningeal disease (LMD). Proton-based vertebral-body-sparing (VBS) CSI has been explored with pediatric patients to minimize hematologic toxicity; however, utilization of VBS in an adult population is limited. We hypothesize that VBS-CSI utilizing volumetric modulated arc therapy (VMAT) will effectively reduce vertebral body dose while minimizing dose to surrounding organs-at-risk (OAR) for adult patients with LMD. METHODS: Ten adult patients with LMD received CSI, 30 Gy in 10 fractions. These patients were initially treated with a variety of VMAT and IMRT treatment techniques. These patients were then retrospectively replanned using VMAT VBS-CSI. For their VBS-CSI replan, full VMAT arcs for the brain fields matched to two spine isocenters for the upper and lower spine were created utilizing limited posterior arcs. The PTV was created with margins of 3mm uniformly around the brain contour and 7mm around the spinal canal. To further decrease the vertebral body dose, an avoid entry and exit contour was created. This structure was a margin on the PTV anteriorly designed to carve dose out of the vertebral bodies while still maintaining coverage to the PTV. RESULTS: All 10 patients had a reduction in vertebral body dose with VMAT VBS-CSI when compared to their initial plan. The mean vertebral dose for the VBS-CSI plans had an average reduction of 33% compared to the initial plans. The mean dose to the small bowel and esophagus were reduced by 46% and 67%, respectively. CONCLUSIONS: VBS-CSI may be utilized to minimize dose to surrounding OARs and vertebral bodies. In this study, VMAT VBS-CSI led to significant reductions in vertebral body dose while also minimizing dose to other OARs. VMAT VBS-CSI may be an acceptable alternative to proton-based VBS-CSI in an adult population with LMD. Prospective evaluation is warranted.